Contribution of Profitability and Company Size to Company Value (A Study of Agricultural Sector Issuers Listed on the Indonesia Stock Exchange in 2019-2023) - Nanda Pratiwi Amran; Herlina Rasjid; Selvi (Majapahit Journal of Islamic Finance and Management, 2025)
This study was conducted to analyze the effect of profitability and company size on company value in the agricultural sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The background of this study is based on fluctuations in agricultural sector stock performance that reflect the dynamics of company value due to changes in profitability and company size. The purpose of this study is to determine the extent of the influence of profitability variables as measured by Net Profit Margin (NPM) and company size as measured by Ln total assets on company value proxied by Tobin's Q. This study uses a quantitative approach with secondary data obtained from the annual financial reports of 12 agricultural companies over five years of observation, with a total of 60 observation data. The analysis was carried out using multiple linear regression with the help of SPSS software version 22. The results show that profitability has a positive and significant effect on company value, while company size has a negative and significant effect on company value. Simultaneously, profitability and company size have a significant effect on company value. These findings indicate that increasing profits has an important role in building investor confidence, while the size of assets does not always reflect the efficiency of company management and performance. The resulting policy implication is the need for company management to focus on increasing profitability to strengthen the company's value in the capital market.